Does the use of different scaffolds have an impact on the therapeutic efficacy of regenerative endodontic procedures? A systematic evaluation and meta-analysis - Feng Yang; Kai Sheng; Lintong Yu; Jun Wang (BMC, 2024)
Abstract Background In the regenerative endodontic procedures, scaffolds could influence the prognosis of affected teeth. Currently, there is controversy regarding the postoperative evaluation of various scaffolds for pulp regeneration. The objective of this study was to access whether other scaffolds, used alone or in combination with blood clot (BC), are more effective than BC in regenerative endodontic procedures. Methods We systematically search the PubMed, the Cochrane Central Register of Controlled Trials (CENTRAL), Embase, and Google Scholar databases. Randomized controlled trials examining the use of BC and other scaffold materials in the regenerative endodontic procedures were included. A random effects model was used for the meta-analysis. The GRADE method was used to determine the quality of the evidence. Results We screened 168 RCTs related to young permanent tooth pulp necrosis through electronic and manual retrieval. A total of 28 RCTs were related to regenerative endodontic procedures. Ultimately, 12 articles met the inclusion criteria and were included in the relevant meta-analysis. Only 2 studies were assessed to have a low risk of bias. High quality evidence indicated that there was no statistically significant difference in the success rate between the two groups (RR=0.99, 95% CI=0.96 to 1.03; 434 participants, 12 studies); low-quality evidence indicated that there was no statistically significant difference in the increase in root length or root canal wall thickness between the two groups. Medium quality evidence indicated that there was no statistically significant difference in pulp vitality testing between the two groups. Conclusions For clinical regenerative endodontic procedures, the most commonly used scaffolds include BC, PRP, and PRF. All the different scaffolds had fairly high clinical success rates, and the difference was not significant. For regenerative endodontic procedures involving young permanent teeth with pulp necrosis, clinical practitioners could choose a reasonable scaffold considering the conditions of the equipment and patients.